Hepatitis C virus internal ribosome entry site RNA contains a tertiary structural element in a functional domain of stem–loop II - Lyons, Alita J. (Oxford University Press, 2001)
The internal ribosome entry site (IRES) of hepatitis C virus (HCV) RNA contains >300 bases of highly conserved 5′-terminal sequence, most of it in the uncapped 5′-untranslated region (5′-UTR) upstream from the single AUG initiator triplet at which translation of the HCV polyprotein begins. Although progress has been made in defining singularities like the RNA pseudoknot near this AUG, the sequence and structural features of the HCV IRES which stimulate accurate and efficient initiation of protein synthesis are only partially defined. Here we report that a region further upstream from the AUG, stem–loop II of the HCV IRES, also contains an element of local tertiary structure which we have detected using RNase H cleavage and have mapped using the singular ability of two bases therein to undergo covalent intra-chain crosslinking stimulated by UV light. This pre-existing element maps to two non-contiguous stretches of the HCV IRES sequence, residues 53–68 and 103–117. Several earlier studies have shown that the correct sequence between bases 45 and 70 of the HCV IRES stem–loop II domain is required for initiation of protein synthesis. Because features of local tertiary structure like the one we report here are often associated with protein binding, we propose that the HCV stem–loop II element is directly involved in IRES action.